2017
DOI: 10.2142/biophysico.14.0_199
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the molecular interactions in DNA damage tolerances

Abstract: DNA damage tolerance (DDT) is a cell function to avoid replication arrest by DNA damage during DNA replication. DDT includes two pathways, translesion DNA synthesis (TLS) and template-switched DNA synthesis (TS). DDT is regulated by ubiquitination of proliferating cell nuclear antigen that binds to double-stranded DNA and functions as scaffold protein for DNA metabolism. TLS is transient DNA synthesis using damaged DNA as a template by error-prone DNA polymerases termed TLS polymerases specialized for DNA dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…This notion has been informed by large data sets which demonstrated that mutations acquired during tumorigenesis can be translated into neoantigens that elicit antitumor immune responses, which subsequently are bolstered by ICB (3,4). In view of these findings we reasoned that intratumoral delivery of low-dose DNA damaging agent calibrated to activate the tumoral mutagenic DNA damage tolerance pathway (5,6), without causing extensive tumoral cell death, might be a productive route to increase tumoral neoantigen formation and reinvigorate the antitumor immune response (2,(7)(8)(9)(10). Activation of the DNA damage tolerance pathway involves recruitment of error-prone translesion synthesis (TLS) DNA polymerases (6,11).…”
Section: Introductionmentioning
confidence: 99%
“…This notion has been informed by large data sets which demonstrated that mutations acquired during tumorigenesis can be translated into neoantigens that elicit antitumor immune responses, which subsequently are bolstered by ICB (3,4). In view of these findings we reasoned that intratumoral delivery of low-dose DNA damaging agent calibrated to activate the tumoral mutagenic DNA damage tolerance pathway (5,6), without causing extensive tumoral cell death, might be a productive route to increase tumoral neoantigen formation and reinvigorate the antitumor immune response (2,(7)(8)(9)(10). Activation of the DNA damage tolerance pathway involves recruitment of error-prone translesion synthesis (TLS) DNA polymerases (6,11).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these observations, we sought to devise therapeutic strategy to increase neoantigens in solid tumors. We have developed an experimental model that utilizes precisely dosed and timed intratumoral administration of the DNA‐damaging drug, cisplatin, which we titrated not to kill tumor cells, but instead inhibit DNA replication catalyzed by high‐fidelity DNA polymerases and activate the DNA damage tolerance pathway (Hashimoto et al, 2017; Ma et al, 2020; Waters et al, 2009), thereby shifting synthesis to error‐prone translesion synthesis (TLS) DNA polymerases (Ghosal & Chen, 2013; Sale et al, 2012; Waters et al, 2009). TLS polymerases‐catalyzed DNA synthesis is predicted to increase the tumor mutation burden and thereby augment tumoral immunogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, the PPI between REV7 and REV3 induces a conformational change in REV7, which promotes binding to REV1-CT. The co-crystal structure of REV1-CT complexed with REV7 (PDB ID 4GK5) demonstrates that the C-terminal tail and the α2-α3 loop of REV1-CT interacts with the C-terminal β-sheet of REV7 (β8 and β8 ), residues of β5 (E101), and the αC-β6 loop (L137 and D138) to form the REV1-REV7 PPI interface (Figure 8) [47,54]. At the REV1-CT/REV7 interface, the side chains of Y1244, S1246, and K1249 (REV1-CT) interact with the side chains of Q200 (β8 ), E101 (β5), E204 (β8 ), E205 (β8 ) and D138 (αC-β6) of REV7 through several hydrogen bonds.…”
Section: Rev1-ct/ Rev7 Ppimentioning
confidence: 99%
“…Mutational studies for REV1-CT at the REV7 interface clearly demonstrate that the hydrophobic interactions contribute more significantly to the PPI than the electrostatic interactions [48]. β5 (E101), and the αC-β6 loop (L137 and D138) to form the REV1-REV7 PPI interface (Figure 8) [47,54]. At the REV1-CT/REV7 interface, the side chains of Y1244, S1246, and K1249 (REV1-CT) interact with the side chains of Q200 (β8"), E101 (β5), E204 (β8"), E205 (β8") and D138 (αC-β6) of REV7 through several hydrogen bonds.…”
Section: Rev1-ct/ Rev7 Ppimentioning
confidence: 99%